БУЛАЕШТСКИЙ ГОВОР И ЕГО ВОЛЬІНСКИЕ И ЗАПАДНОПОЛЕССКИЕ ПАРАЛЛЕЛИ: ПРЕДВАРИТЕЛЬНЬІЕ ЗАМЕЧАНИЯ - Романчук, Алексей; Aleksey, A. (Волинський національний університет імені Лесі Українки, 2010)
У статті проаналізовані волинсько-західнополіські паралелі української говірки села Булаєшти (Орхейський район, республіка Молдова). . The author makes lexical comparisons of Bulaesty Ukrainian dialect (Orhei District, Republic of Moldova) and the ones from Volhynia-West Polesye region. Despite a big territorial distance, some interesting similarities between Bulaesty and Volhynia-West Polesye dialects were found. A large share of these similarities come from Sylnoe village (Kivertsy district, Volhynia region). Thus, further inquiries into this issue seem to be very promising.
Keywords: говірка; волинсько-західнополіські паралелі; територіальна віддаленість; Volhynia-West Polesye parallels; patois; territorial remoteness